Influence of a Helium–Nitrogen RF Plasma Jet on Onion Seed Germination - Agnieszka Starek-Wójcicka; Agnieszka Sagan; Piotr Terebun; Michał Kwiatkowski; Piotr Kiczorowski; Joanna Pawlat (Applied Sciences, 2020)
This paper presents an experiment using a radio frequency atmospheric pressure plasma jet to generate cold plasma for pre-sowing stimulation of Wolska onion seeds. Impact of the He + N2 afterglow plasma on germination was investigated. Eight groups of seeds characterized by different exposure times (2, 5, 10, 15, 60, 120, 240, and 480 s) and distance from the electrodes (20 mm and 50 mm) were used. Pre-sowing plasma stimulation of the seeds improved the germination capacity and germination energy for all tested groups, relative to control. The impact of radio frequency plasma on the onion seed germination parameters was statistically significant. The highest germination parameters were obtained for seeds stimulated for 240 s at a distance of 50 mm. No significant differences in physical and morphological properties of onion seeds were found.